ChemInform Abstract: Intramolecular Cascade Lactone Cyclization of Dicoumarol Derivatives Promoted by Tributyltin Chloride. Issue 32 (12th August 2014) - Rehman, Sadia; Ikram, Muhammad; Subhan, Fazle
Abstract: A novel catalytic route for the cyclization of dicumarols to obtain pyran derivatives using a tin organometallic compound as catalyst is reported.